Food safety in milk markets of smallholder farmers in Tanzania: A case study of peri-urban wards in Temeke - Kilango, K.; Makita, K.; Kurwijila, Lusato R.; Grace, Delia (2011)
marketed by smallholder farmers in peri-urban wards of Temeke Municipality, Dar es Salaam Tanzania between January 2010 to March 2010. Methods: A total of 120 milk samples from farmers (n=69), milk vendors (n=7) and milk kiosks (n=44) were collected from four randomly selected wards to assess presence of Staphylococcus aureus. At randomly selected milk selling shops,120 consumers were interviewed on their perception regarding safety of milk. Standard methods were used to isolate S. aureus in milk samples. Data were analyzed using SPSS version 12.0. Results: About 1,792 litres (90% CI: 1 337-2,358) of milk are sold everyday in kiosks of Temeke municipality peri-urban wards. Out of this amount, 407 litres (90% CI: 119-799) was found to be contaminated with S. aureus. Exposure assessment showed that the probability of purchasing contaminated milk was 0.227 (90% CI: 0.062-0.436). Every day, 953 (90% CI: 718-1,249) people purchase milk from kiosks in peri-urban Temeke, and among them, 217 (90% CI: 62-427) people were estimated to purchase contaminated milk. The Total Bacterial Count (TBC) was also determined.The overall picture at both the production and market levels was that bacterial counts increase (and subsequently, milk quality decreases) as milk passes through increasing numbers of intermediaries. Other organisms isolated from the milk samples include Bacillus spp., Escherichia coli, Proteus spp., Enterobacter spp., Corynebacterium spp. and Micrococcus spp. Participatory risk assessment showed that consumers knowledge on health risk associated with milk consumption was high (71.67%). Most of them reported stomach problems/diarrhea as major health risk one can encounter from drinking milk. This could be the reason why most of consumers prefer boiled milk served hot as they believe boiling of milk kills most of pathogenic bacteria. Poisoning from S. aureus through milk consumption occurs when humans consume enterotoxin produced by the pathogens.